2012
DOI: 10.1007/s11051-012-0737-4
|View full text |Cite
|
Sign up to set email alerts
|

Fluidization of nanopowders: a review

Abstract: Nanoparticles (NPs) are applied in a wide range of processes, and their use continues to increase. Fluidization is one of the best techniques available to disperse and process NPs. NPs cannot be fluidized individually; they fluidize as very porous agglomerates. The objective of this article is to review the developments in nanopowder fluidization. Often, it is needed to apply an assistance method, such as vibration or microjets, to obtain proper fluidization. These methods can greatly improve the fluidization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
161
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 197 publications
(165 citation statements)
references
References 110 publications
1
161
0
1
Order By: Relevance
“…This strongly suggests that the formation of airborne silica nanoparticles during fluidization of Stöber-coated beads can be attributed to the detachment of individual nanoparticles from the glass surface. Although additional aggregation could be expected from the gas-phase agglomeration of the nanoparticles released, as Lushnikov (2010), Eggersdorfer andPratsinis (2012), andVan Ommen et al (2012) reported, this is unnoticed at least for 100 nm Stöber-silica-coated glass beads.…”
Section: Generation Of Nanoparticle Aerosolsmentioning
confidence: 95%
See 1 more Smart Citation
“…This strongly suggests that the formation of airborne silica nanoparticles during fluidization of Stöber-coated beads can be attributed to the detachment of individual nanoparticles from the glass surface. Although additional aggregation could be expected from the gas-phase agglomeration of the nanoparticles released, as Lushnikov (2010), Eggersdorfer andPratsinis (2012), andVan Ommen et al (2012) reported, this is unnoticed at least for 100 nm Stöber-silica-coated glass beads.…”
Section: Generation Of Nanoparticle Aerosolsmentioning
confidence: 95%
“…Indeed, the continuous addition of bed material leads to longer periods of stable aerosol generation and it was originally proposed by Prenni et al (2000) for generating submicrometer soot aerosols from a bronze-bead fluidized bed. It should be realized that fluidizing nanomaterials is a challenging task, as shown in a recent review (Van Ommen et al 2012), and this is the reason why most of the fluidized bed aerosol generators (FBAGs) use a second, coarse solid as a co-adjuvant. Nanoparticles from fluidized bed devices form agglomerates with a particle size distribution that depends on the material properties, primary particle size, characteristics of the generator device, and operating conditions (Van Ommen et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Although it may sound counterintuitive, nanopowders can indeed be fluidized. In contrast to particles of say 200 μm, however, nanoparticles are not fluidized individually but as agglomerates: very dilute structures of around 200 μm consisting of ~10 10 primary particles (van Ommen et al, 2012). Despite the fact that the fluidized bed reactor provided a good scalability potential in terms of the batch handling capabilities, the high total surface area of the powdersand the subsequent need for large amounts of precursor dosing (due to the residence time of the gaseous precursor in the fluidized bed)-called for research focussed on more efficient utilization of the precursor.…”
Section: Reactor Technologymentioning
confidence: 99%
“…Since many of the powders used as substrates exhibit cohesive behaviour, fluidization assistance methods such as stirring or vibration are typically required. van Ommen et al (2012) give an overview of the various assistance methods to fluidize nanopowders. Although it may sound counterintuitive, nanopowders can indeed be fluidized.…”
Section: Reactor Technologymentioning
confidence: 99%
“…to produce coated nanoparticles [1]. Due to van der Waals forces, dominant at the nano-scale, nanoparticles do not fluidize individually but forming agglomerates [2].…”
Section: Introductionmentioning
confidence: 99%